الأهلية القانونية للعقود الإلكترونية في القانون الإماراتي - Khalid Hassan Salim Hassan Alqaydi; Syaryanti Hussin; Fadhlina Alias (WorldConferences.net, 2024)
This study dealt with the issue of eligibility in the electronic contract, as the UAE legislator did not regulate special provisions in the eligibility of contractors through electronic means. The eligibility within the scope of electronic contracting is the same as in the ordinary contract, but it turns out that eligibility within the scope of electronic contract raises many problems and difficulties stemming from the electronic nature of the media through which the electronic contract is concluded first, and because this contract is concluded between absentees secondly, and the study recommended the Emirati legislator to amend The Electronic Transactions Law has special texts regulating eligibility as it is important in electronic contracting, as the reference to general rules does not keep pace with the tremendous development in remote contracting, especially since there are many problems raised by the electronic contract that differ from traditional contracts, and also, the contract in the electronic environment appeared in a larger and larger way on various Countries of the world .